Dental restoration material and preparation method thereof
By using monomers such as UDMA, TEGDMA and THFMA in dental restoration materials and using fine process treatment, the problem of insufficient bonding performance of traditional dental restoration materials is solved, and the bonding performance and durability of the materials are significantly improved.
Patent Information
- Application Number
- CN202411955438.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-03-28
AI Technical Summary
Traditional dental restorative materials have shortcomings in bonding performance, resulting in unsatisfactory bonding strength between the restoration and dental tissue, which is prone to loosening and falling off.
Carbamate bismethacrylate (UDMA), triethylene glycol dimethacrylate (TEGDMA) and tetrahydrofuran methacrylate (THFMA) are used as monomers, and the adhesion performance of dental restoration materials is improved by precisely controlling the dosage and process parameters of each monomer, such as ball milling, drying, pre-pressing molding and thermal curing molding.
It significantly improves the adhesive properties of dental restoration materials, enhances their adhesion to dental tissue, reduces the risk of loosening and falling off, and ensures the durability of the material in complex oral environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of dental materials, in particular to a dental restoration material and a preparation method thereof. Background Art
[0002] The materials used in early dental restorations were mainly metals (such as silver-mercury alloys), ceramics, and natural materials. Although metal materials have a certain strength, they have poor biocompatibility and are prone to cause adverse reactions such as gum discoloration and allergies. In addition, the release of metal ions poses potential health risks. Ceramic materials have relatively good aesthetics and biocompatibility, but their brittleness makes them prone to breakage when subjected to chewing forces, which greatly limits their application in posterior tooth restorations. Natural materials are difficult to use on a large scale in clinical practice due to their limited sources and unstable performance.
[0003] With the continuous development of materials science, acrylic resins have gradually come to the fore. Early composite resins consisted of a resin matrix (such as methyl methacrylate copolymer) and an inorganic filler (such as silica). Although the performance of the material was improved to a certain extent, it still had obvious deficiencies in terms of mechanical properties, wear resistance, adhesion and stability.
[0004] In order to improve performance, monomers such as bisphenol A dimethacrylate (Bis-GMA) and triethylene glycol dimethacrylate (TEGDMA) were introduced into the restoration materials, which effectively increased the cross-linking density and mechanical strength of the materials. However, traditional restoration materials still face a series of severe challenges. In terms of bonding performance, the bonding strength between the restoration and the tooth tissue is not ideal, and it is easy to loosen and fall off during long-term use. Summary of the invention
[0005] Based on this, it is necessary to provide a dental restoration material and a preparation method thereof to improve the bonding performance.
[0006] One of the objects of the present invention is to provide a dental restoration material, the scheme is as follows:
[0007] A dental restoration material comprising the following components:
[0008] 11-13.9 parts by mass of urethane dimethacrylate, 4.5-6.8 parts by mass of triethylene glycol dimethacrylate, 0.6-0.9 parts by mass of tetrahydrofuran methacrylate, 0.5-3 parts by mass of initiator and 20-40 parts by mass of inorganic filler.
[0009] In one embodiment, the content of urethane dimethacrylate is 11-13 parts by mass, the content of triethylene glycol dimethacrylate is 4.8-6.8 parts by mass, and the content of tetrahydrofuran methacrylate is 0.9 parts by mass.
[0010] In one embodiment, the initiator is selected from one or more of BPO (dibenzoyl peroxide) and AIBN.
[0011] In one embodiment, the inorganic filler is selected from one or more of glass powder, silicon oxide, silicon dioxide, and zirconium oxide.
[0012] In one embodiment, the dental restoration material further comprises an additive, and the content of the additive is less than 5 parts by mass.
[0013] In one embodiment, the additives include one or more of a colorant, a stabilizer, and a UV absorber.
[0014] In one embodiment, the content of the additive is 0.01 to 5 parts by weight.
[0015] Another object of the present invention is to provide a method for preparing the dental restoration material of any one of the above embodiments, the method being as follows:
[0016] A method for preparing a dental restoration material comprises the following steps:
[0017] Dispersing carbamate dimethacrylate triethylene glycol dimethacrylate, tetrahydrofuran methacrylate and the initiator in a solvent to obtain a dispersion;
[0018] Adding the inorganic filler into the dispersion and grinding the mixture to obtain a mixed material;
[0019] Drying the mixed material to obtain a dry material;
[0020] The dried material is subjected to a pre-pressing and molding process to obtain a pre-pressing and molding material;
[0021] The pre-pressed molding material is subjected to a heat curing molding process to obtain the dental restoration material.
[0022] In one embodiment, the solvent is alcohol; and the temperature of the drying process is controlled at 50°C-60°C.
[0023] In one embodiment, the grinding process includes ball milling, the rotation speed of the ball milling is above 300 rpm, and the ball milling time is 1-2 hours.
[0024] In one embodiment, the process parameters of the pre-pressing process include:
[0025] The applied pressure is 20MPa-50MPa.
[0026] In one embodiment, the process parameters of the thermal curing process include:
[0027] The applied pressure is 140MPa-180MPa, the curing temperature is 120°C-140°C, and the curing time is 2 hours-6 hours.
[0028] Compared with the traditional solution, the above dental restoration material and preparation method thereof have the following beneficial effects:
[0029] The monomers selected in the present invention include urethane dimethacrylate (UDMA), triethylene glycol dimethacrylate (TEGDMA) and tetrahydrofuran methacrylate (THFMA), and the amount of each monomer is precisely controlled so that the above monomers cooperate with each other to achieve the best performance effect. Among them, the amount of UDMA is controlled at 11-13.9 parts, which can give the dental restoration material good flexibility and mechanical strength. During the curing process of the dental restoration material, it can effectively reduce the shrinkage stress, enhance the compatibility of the dental restoration material with the tooth tissue, and ensure the durability of the dental restoration material during long-term use in the complex environment of the oral cavity. The amount of TEGDMA is controlled at 4.5-6.8 parts, and its main function is to accurately adjust the viscosity of the resin system, so that the resin system has good fluidity during the processing process, so that the various components can be fully mixed and evenly mixed, and the consistency of the material performance is guaranteed. The dosage of THFMA is controlled at 0.6-0.9 parts. As a key reactive diluent, on the one hand, it can reduce the viscosity of the resin system to facilitate processing and molding; on the other hand, after participating in the polymerization reaction, it can significantly increase the cross-linking density of the polymer network; on the third hand, the tetrahydrofuran ring in its molecule has a high polarity, which can form hydrogen bonds or van der Waals forces with polar groups on the tooth surface (such as hydroxyl, carboxyl, etc.), thereby significantly increasing the adhesion of the composite resin to the tooth surface and greatly improving the bonding performance of dental restoration materials. DETAILED DESCRIPTION
[0030] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. The purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0031] It should be noted that when an element is referred to as being "disposed on" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.
[0032] In the description of the present invention, it should be understood that the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number or order of the indicated technical features.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0034] A dental restoration material according to an embodiment of the present invention comprises the following components:
[0035] 11-13.9 parts by mass of urethane dimethacrylate, 4.5-6.8 parts by mass of triethylene glycol dimethacrylate, 0.6-0.9 parts by mass of tetrahydrofuran methacrylate, 0.5-3 parts by mass of initiator and 20-40 parts by mass of inorganic filler.
[0036] In the dental restoration material of the present invention, the content of carbamate dimethacrylate is 11-13.9 mass parts, for example, 11.1 mass parts, 11.3 mass parts, 11.5 mass parts, 11.7 mass parts, 11.9 mass parts, 12.1 mass parts, 12.3 mass parts, 12.5 mass parts, 12.7 mass parts, 12.9 mass parts, 13.1 mass parts, 13.3 mass parts, 13.5 mass parts, 13.7 mass parts, 13.9 mass parts, etc.
[0037] In the dental restoration material of the present invention, the content of triethylene glycol dimethacrylate is 4.5-6.8 mass parts, for example, 4.5 mass parts, 4.6 mass parts, 4.8 mass parts, 4.9 mass parts, 5 mass parts, 5.2 mass parts, 5.4 mass parts, 5.6 mass parts, 5.8 mass parts, 6 mass parts, 6.4 mass parts, 6.8 mass parts, etc.
[0038] In the dental restoration material of the present invention, the content of tetrahydrofuran methacrylate is 0.6-0.9 parts by mass, for example, 0.6 parts by mass, 0.65 parts by mass, 0.7 parts by mass, 0.75 parts by mass, 0.8 parts by mass, 0.85 parts by mass, 0.9 parts by mass, etc.
[0039] The monomers selected in the present invention include urethane dimethacrylate (UDMA), triethylene glycol dimethacrylate (TEGDMA) and tetrahydrofuran methacrylate (THFMA), and the amount of each monomer is precisely controlled so that the above monomers cooperate with each other to achieve the best performance effect.
[0040] Among them, the amount of UDMA is controlled at 11-13.9 parts, which can give dental restoration materials good flexibility and mechanical strength. During the curing process of dental restoration materials, it can effectively reduce shrinkage stress, enhance the compatibility of dental restoration materials with tooth tissues, and ensure the durability of dental restoration materials during long-term use in complex oral environments. The amount of TEGDMA is controlled at 4.5-6.8 parts. Its main function is to accurately adjust the viscosity of the resin system, so that the resin system has good fluidity during processing, so that the components can be fully mixed and uniform, and the consistency of material performance is guaranteed. The amount of THFMA is controlled at 0.6-0.9 parts. As a key reactive diluent, on the one hand, it can reduce the viscosity of the resin system for easy processing and molding; on the other hand, after participating in the polymerization reaction, it can significantly increase the cross-linking density of the polymer network; on the third hand, the tetrahydrofuran ring in its molecule has a high polarity, which can form hydrogen bonds or van der Waals forces with polar groups (such as hydroxyl groups, carboxyl groups, etc.) on the surface of the teeth, thereby significantly increasing the adhesion of the composite resin on the surface of the teeth and greatly improving the bonding performance of dental restoration materials.
[0041] Through the above-mentioned precise proportion matching, efficient synergistic cooperation is achieved between the various monomers to achieve the best performance effect. This is a significant feature of the present invention that distinguishes it from traditional technologies in terms of monomer selection and application.
[0042] Traditional reactive diluents such as glycidyl methacrylate (GMA) can reduce the viscosity of the resin to a certain extent, but their effect on improving bonding performance is relatively limited and may also have a negative impact on other properties, such as reducing mechanical strength or biocompatibility. Excessive use may even lead to incomplete polymerization.
[0043] The present invention uses THFMA as a reactive diluent. The tetrahydrofuran ring in its molecule gives THFMA a higher polarity, which enables it to form a strong interaction with the polar groups on the tooth surface, thereby significantly increasing the adhesion of the composite resin to the tooth surface. Compared with traditional diluents, THFMA can not only effectively reduce the viscosity of the resin system to facilitate processing and molding, but more importantly, after participating in the polymerization reaction, it can increase the cross-linking density of the polymer network. The highly cross-linked network structure makes the composite resin more firmly bonded to the tooth surface, and can form a stable bonding interface, effectively resisting the influence of various factors such as chewing force in the mouth and saliva flushing, thereby significantly reducing the risk of loosening and falling off of dental restoration materials.
[0044] In some examples, the content of urethane dimethacrylate is 11-13 parts by mass, the content of triethylene glycol dimethacrylate is 4.8-6.8 parts by mass, and the content of tetrahydrofuran methacrylate is 0.9 parts by mass. In this ratio range, better bonding strength can be obtained.
[0045] The initiator is used to initiate the polymerization of monomers to form a resin. The content of the initiator is, for example, 0.5 mass parts to 3 mass parts. This dosage range can ensure that the polymerization reaction proceeds smoothly, the monomers are fully polymerized, and the curing quality of the dental restoration material is guaranteed. In some examples, the content of the initiator is, for example, 1 mass part to 2 mass parts. In some specific examples, the content of the initiator is, for example, 0.5 mass parts, 0.8 mass parts, 1 mass part, 1.2 mass parts, 1.5 mass parts, 1.8 mass parts, 2 mass parts, 2.2 mass parts, 2.5 mass parts, 2.8 mass parts, 3 mass parts, etc.
[0046] For example, the initiator may be, but is not limited to, one or more of BPO (dibenzoyl peroxide) and AIBN (azobisisobutyronitrile).
[0047] Inorganic fillers can improve the mechanical strength and other properties of dental restoration materials. The content of inorganic fillers is, for example, 20 parts by mass to 40 parts by mass. Reasonable content of inorganic fillers helps to balance the mechanical properties, processing properties, biocompatibility and other properties of composite resins. In some examples, the content of inorganic fillers is, for example, 25 parts by mass to 35 parts by mass. In some specific examples, the content of inorganic fillers is 20 parts by mass, 22 parts by mass, 24 parts by mass, 26 parts by mass, 28 parts by mass, 30 parts by mass, 32 parts by mass, 34 parts by mass, 36 parts by mass, 38 parts by mass, 40 parts by mass, etc.
[0048] Optionally, the inorganic filler includes, but is not limited to, one or more of glass powder, silicon oxide, silicon dioxide, and zirconium oxide. Among them, glass powder has a good reinforcing effect, and its addition plays an important role in improving the performance of the composite resin. It can effectively improve the rigidity of the resin and enhance the mechanical strength of the dental restoration material, so that it can better withstand the external forces in the oral cavity such as chewing force. At the same time, glass powder has excellent chemical stability, which helps to improve the durability of the composite resin in the complex chemical environment of the oral cavity and maintain the stable performance of the dental restoration material for a long time.
[0049] In some examples, the dental restoration material further comprises an additive. The content of the additive is, for example, less than 5 parts by mass. In some examples, the additive is added in an amount of 0.01 parts by mass to 5 parts by mass, specifically, for example, 0.01 parts by mass, 0.05 parts by mass, 0.1 parts by mass, 0.3 parts by mass, 0.5 parts by mass, 0.8 parts by mass, 1 part by mass, 2 parts by mass, 3 parts by mass, 4 parts by mass, 5 parts by mass, etc.
[0050] Additives may include, but are not limited to, colorants, stabilizers, ultraviolet absorbers, etc. The addition of colorants can adjust the color of the composite resin so that it can accurately match the color of the patient's natural teeth, meet the personalized needs of different patients for the aesthetics of dental restoration materials, and improve the satisfaction of restoration treatment. Stabilizers can, for example, improve the thermal stability of dental restoration materials. Ultraviolet absorbers can improve the ability of dental restoration materials to resist ultraviolet aging.
[0051] In other examples, the dental restoration material may not contain additives, that is, the amount of additives added is zero.
[0052] Furthermore, the present invention also provides a method for preparing any of the above-mentioned dental restoration materials.
[0053] The following steps are involved:
[0054] Step S1, dispersing each acrylate monomer, initiator and additive in a solvent to obtain a dispersion;
[0055] Step S2, adding an inorganic filler into the dispersion and grinding the mixture to obtain a mixed material;
[0056] Step S3, drying the mixed material to obtain a dried material;
[0057] Step S4, pre-pressing and molding the dried material to obtain a pre-pressed material;
[0058] Step S5, subjecting the pre-pressed molding material to a thermal curing molding process to obtain a dental restoration material.
[0059] In some examples, in step S1 , the solvent used is alcohol.
[0060] In some examples, in step S1, a magnetic stirrer is used to stir and mix at room temperature for 30 minutes to 60 minutes. This process allows each component to be fully dissolved and dispersed to form a uniform mixed solution, laying a good foundation for subsequent mixing with fillers.
[0061] In some examples, in step S2, the grinding process includes ball milling. During the ball milling process, the inorganic filler can be evenly dispersed in the system, and the particles are further refined through grinding and collision, ensuring that the performance of the composite resin is uniform and consistent, thereby improving the overall quality of the material.
[0062] In some examples, the ball milling process has a rotation speed of 300 rpm or more, such as 300 rpm to 600 rpm, and a ball milling time of 1 hour to 2 hours.
[0063] In some examples, in step S3, the drying temperature is controlled at 50°C-60°C, specifically 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, etc. The drying time is more than 8 hours, for example, 8 hours to 24 hours.
[0064] In step S4, the pre-pressing process can be performed using a press machine. The pre-pressing process allows the material to be initially formed, which is convenient for subsequent thermal curing treatment and helps to improve the density and uniformity of the material.
[0065] In some examples, in step S4, the process parameters of the pre-pressing process include:
[0066] The applied pressure is 20 MPa-50 MPa, and specific examples include 20 MPa, 25 MPa, 30 MPa, 35 MPa, 40 MPa, 45 MPa, and 50 MPa.
[0067] In step S5, the heat curing molding process can be performed by a hot press. Under high temperature and high pressure, the monomer undergoes a polymerization reaction, so that the composite resin is completely cured and molded to obtain a processable composite resin product with good performance. This process ensures the final performance of the dental restoration material, enabling it to meet the strict requirements of oral restoration.
[0068] In some examples, in step S5, the process parameters of the thermal curing process include:
[0069] The applied pressure is 140MPa-180MPa, for example, 140MPa, 145MPa, 150MPa, 155MPa, 160MPa, 165MPa, 170MPa, 175MPa, 180MPa, etc.; the curing temperature is 120℃-140℃, for example, 120℃, 125℃, 130℃, 135℃, 140℃; the curing time is 2 hours-6 hours, for example, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, etc.
[0070] The above examples provide fine control over each link of the preparation process. In the dispersion and mixing stage, a magnetic stirrer is used for stirring at room temperature, and the stirring time is strictly controlled within 30-60 minutes. This operation can ensure that the components such as UDMA, TEGDMA, THFMA and pigments are fully dissolved and evenly dispersed in the alcohol medium to form a uniform and stable resin-pigment mixture, which provides a good foundation for subsequent mixing with fillers. When the filler addition and dispersion (ball milling) step is performed, the pre-prepared glass powder is slowly added to the above mixture, and then the mixture is transferred to the ball mill, and the speed of the ball mill is accurately set to more than 300rpm, and the ball milling time is controlled to 1-2 hours. During the ball milling process, the glass powder can be evenly dispersed in the resin system under the action of the alcohol medium, and the glass powder particles are further refined by grinding and collision, thereby ensuring the uniform performance of the composite resin and effectively improving the overall quality of the material. Subsequent drying, pre-pressing and thermosetting steps also follow strict process parameter settings.
[0071] These process measures effectively solve the problems of viscosity and curing time that are difficult to control during processing of existing materials, and significantly improve the fluidity and plasticity of composite resins during processing. This enables clinicians to process and shape dental restoration materials more conveniently and accurately during operation, so that they can better adapt to the specific morphology and restoration needs of patients' teeth, and improve clinical operation efficiency and the accuracy of restoration effects. This all-round fine control of the preparation process ensures the high quality and performance stability of the product, and is one of the key factors for the successful preparation of high-performance composite resins in the present invention.
[0072] The following specific examples are provided to further illustrate the present invention. The present invention provides the following specific examples for a better understanding of the present invention, but is not limited to the specific implementation methods and does not limit the protection scope of the present invention.
[0073] Example 1
[0074] This embodiment provides a dental restoration material and a preparation method thereof.
[0075] The dental restoration material of this embodiment comprises the following components:
[0076] Acrylate monomer UDMA 13.0g, TEGDMA 4.8g, THFMA 0.9g, initiator BPO 0.1g, inorganic filler silica 80g.
[0077] The method for preparing the dental restoration material of this embodiment comprises the following steps:
[0078] Step 1: Add acrylate monomer, initiator and colorant to an appropriate amount of alcohol, stir and mix using a magnetic stirrer at room temperature for 40 minutes to obtain a dispersion.
[0079] Step 2, adding an inorganic filler to the above dispersion, and transferring it to a ball mill for grinding, setting the speed of the ball mill to 300 rpm, and the ball milling time to 2 hours to obtain a mixed material.
[0080] Step 3, placing the above mixed material in an oven for drying, the drying temperature is controlled at 50° C., the drying time is 8 hours, and a dry material is obtained.
[0081] Step 4, putting the above-mentioned dry material into a mold, placing it in a press for pre-pressing and molding treatment, the pressure is 30MPa, to obtain a pre-pressed molded material.
[0082] Step 5, placing the pre-pressed material into a hot press for heat curing treatment, applying a pressure of 150 MPa, a curing temperature of 130° C., and a curing time of 4 hours to obtain a dental restoration material.
[0083] Example 2
[0084] The difference between this embodiment and embodiment 1 is that:
[0085] (1) Dental restorative materials include the following components:
[0086] Acrylate monomer UDMA 12.5g, TEGDMA 5.5g, THFMA 0.8g, initiator BPO 0.2g, inorganic filler silica 80g.
[0087] (2) In step 5 of the preparation method, the pressure applied in the thermal curing molding process is 130 MPa, the curing temperature is 110° C., and the curing time is 5 hours.
[0088] Example 3
[0089] The difference between this embodiment and embodiment 1 is that:
[0090] (1) Dental restorative materials include the following components:
[0091] Acrylate monomer UDMA 12.0g, TEGDMA 6.0g, THFMA 0.7g, initiator BPO 0.1g, inorganic filler silica 80g.
[0092] (2) In step 5 of the preparation method, the pressure applied in the thermal curing molding process is 150 MPa, the curing temperature is 130° C., and the curing time is 3.5 hours.
[0093] Example 4
[0094] The difference between this embodiment and embodiment 1 is that:
[0095] (1) Dental restorative materials include the following components:
[0096] Acrylate monomer UDMA 11.5g, TEGDMA 6.5g, THFMA 0.6g, initiator BPO 0.2g, inorganic filler silica 80g.
[0097] (2) In step 5 of the preparation method, the pressure applied in the thermal curing molding process is 130 MPa, the curing temperature is 110° C., and the curing time is 5 hours.
[0098] Example 5
[0099] The difference between this embodiment and embodiment 1 is that:
[0100] (1) Dental restorative materials include the following components:
[0101] Acrylate monomer UDMA 11.0g, TEGDMA 6.8g, THFMA 0.9g, initiator BPO 0.3g, inorganic filler silica 80g.
[0102] (2) In step 5 of the preparation method, the pressure applied in the thermal curing molding process is 130 MPa, the curing temperature is 110° C., and the curing time is 5 hours.
[0103] Example 6
[0104] The difference between this embodiment and embodiment 1 is that:
[0105] Dental restorative materials contain the following components:
[0106] Acrylate monomer UDMA 10.5g, TEGDMA 6.2g, THFMA 0.76g, initiator BPO 0.1g, inorganic filler silica 80g.
[0107] (2) In step 5 of the preparation method, the pressure applied in the thermal curing molding process is 170 MPa, the curing temperature is 140° C., and the curing time is 3 hours.
[0108] Comparative Example 1
[0109] The difference between this comparative example and Example 1 is:
[0110] Dental restorative materials contain the following components:
[0111] Acrylate monomer UDMA 12.0g, TEGDMA 7.0g, bisphenol A dimethacrylate (BisGMA) 2.0g, initiator BPO 0.1g, inorganic filler silica 80g.
[0112] (2) In step 5 of the preparation method, the pressure applied in the thermal curing molding process is 130 MPa, the curing temperature is 110° C., and the curing time is 5 hours.
[0113] Comparative Example 2
[0114] The difference between this comparative example and Example 1 is:
[0115] Dental restorative materials contain the following components:
[0116] Acrylate monomer UDMA 13.9g, TEGDMA 4.8g, initiator BPO 0.1g, inorganic filler silica 80g.
[0117] Comparative Example 3
[0118] The difference between this comparative example and Example 1 is:
[0119] Dental restorative materials contain the following components:
[0120] Acrylate monomer UDMA 12.0g, TEGDMA 6.0g, THFMA 2g, initiator BPO 0.1g, inorganic filler silica 80g.
[0121] The following performance tests were performed on the dental restoration materials prepared in the above examples and comparative examples.
[0122] Bond strength test
[0123] The bonding strength test of the samples prepared in the above embodiments and comparative examples was carried out using a universal material testing machine and in accordance with the method in ISO10477 standard. The specific operation process is: the sample is precisely bonded to the enamel surface, an external force is applied at a specified loading speed, and the force required for the sample to detach from the enamel surface is measured, which is used as a measure of the bonding strength.
[0124] The specific test results are shown in Table 1.
[0125] Table 1
[0126]
[0127] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0128] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A dental restorative material, characterized in that: The raw materials include the following components: 11-13.9 parts by mass of urethane dimethacrylate, 4.5-6.8 parts by mass of triethylene glycol dimethacrylate, 0.6-0.9 parts by mass of tetrahydrofuran methacrylate, 0.5-3 parts by mass of initiator and 20-40 parts by mass of inorganic filler.
2. The dental restorative material according to claim 1, characterized in that In the dental restoration material, the content of urethane dimethacrylate is 11-13 parts by mass, the content of triethylene glycol dimethacrylate is 4.8-6.8 parts by mass, and the content of tetrahydrofuran methacrylate is 0.9 parts by mass.
3. The dental restorative material according to claim 1, characterized in that The initiator is selected from one or more of BPO and AIBN.
4. The dental restorative material according to claim 1, characterized in that The inorganic filler is selected from one or more of glass powder, silicon oxide, silicon dioxide and zirconium oxide.
5. The dental restorative material according to any one of claims 1 to 4, characterized in that The dental restoration material further comprises an additive, wherein the content of the additive does not exceed 5 parts by mass.
6. The dental restorative material according to claim 5, characterized in that The dental restoration material meets at least one of the following characteristics (1) to (2): (1) The additives include one or more of a colorant, a stabilizer and an ultraviolet absorber; (2) The content of the additive is 0.01 to 5 parts by weight.
7. A method for preparing a dental restorative material according to any one of claims 1 to 6, characterized in that: The following steps are involved: Dispersing carbamate dimethacrylate triethylene glycol dimethacrylate, tetrahydrofuran methacrylate and the initiator in a solvent to obtain a dispersion; Adding the inorganic filler into the dispersion and grinding the mixture to obtain a mixed material; Drying the mixed material to obtain a dry material; The dried material is subjected to a pre-pressing and molding process to obtain a pre-pressing and molding material; The pre-pressed molding material is subjected to a heat curing molding process to obtain the dental restoration material.
8. The preparation method according to claim 7, characterized in that: The preparation method meets at least one of the following characteristics (1) to (2): (1) The solvent is alcohol; the temperature of the drying process is controlled at 50°C-60°C; (2) The grinding treatment includes ball milling treatment, the rotation speed of the ball milling treatment is above 300 rpm, and the ball milling time is 1 hour to 2 hours.
9. The preparation method according to claim 7, characterized in that: The process parameters of the pre-pressing process include: The applied pressure is 20MPa-50MPa.
10. The preparation method according to any one of claims 7 to 9, characterized in that: The process parameters of the thermal curing molding process include: The applied pressure is 140MPa-180MPa, the curing temperature is 120°C-140°C, and the curing time is 2 hours-6 hours.